2016
DOI: 10.1016/j.virusres.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Immune gene expression in swine macrophages expressing the Torque Teno Sus Virus1 (TTSuV1) ORF-1 and 2 proteins

Abstract: Torque Teno viruses (TTVs) are small DNA viruses which are ubiquitous in nature. Recent reports indicate that swine torque teno viruses (TTSuVs) can act as primary pathogens or play a role in exacerbating co-infections. However, very little is known about the TTSuV host-viral interaction or how they so successfully establish chronic infections in the host. To determine whether the major viral proteins can modulate host immunity, recombinant TTSuV1 ORF1 and 2 proteins were expressed in a swine macrophage cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…IL-4 is involved in all major aspects of inflammatory responses 18 . IL-10, an anti-inflammatory cytokine, down-regulates macrophage activity in swine 19 , 20 . In this study, the mRNA abundance of IL-8 in the kidney and IL-6 in the spleen were significantly higher in the lysine-restricted group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 is involved in all major aspects of inflammatory responses 18 . IL-10, an anti-inflammatory cytokine, down-regulates macrophage activity in swine 19 , 20 . In this study, the mRNA abundance of IL-8 in the kidney and IL-6 in the spleen were significantly higher in the lysine-restricted group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although prevalence is a multifactorial variable, the marked prevalence differences reported worldwide, which range from 80% to 90% in Spain and China (McKweon, Fenaux, Halbur, & Meng, ) to lower values of 33%–40% in the United States (McKweon et al., ) and Mexico (Vargas, ) might be related to the great variety of systems and types of producers in these countries, where in Mexico even a large number of small producers can be found in the urban area.. Such variations and exchange of Lysine among different genotypes of TTSuV1a may influence host's ability to start an immune response since an ORF2‐associated suppression of NF‐κβ has been described (Zheng et al., ; Singh & Ramamoorthy, ).…”
Section: Discussionmentioning
confidence: 99%
“…A conformational change in the precise site of dominant epitopes can have a relevant impact in immune function, particularly on immunoglobulin production. It has been found that several IgGs are able to bind to ORF1 (Singh & Ramamoorthy, ; Jarasova & Celer, ; Liu et al., ; Giménez‐Lirola et al., ; Nieto, Martínez‐Guinó, Jiménez‐Melsio, Segalés, & Kekarainen, ) and ORF2 products (Jiménez‐Melsió et al., ) from TTSuV1a and TTSuV1b.…”
Section: Discussionmentioning
confidence: 99%
“…All reagents and PK15N and ST cells used were previously tested and found to be negative for TTSuVs and PCVs. Recombinant TTSuV1 (Gen Bank KT037083) and PCV2b 41513 (Gen Bank ALD62452) were rescued by transfection as previously described ( Singh and Ramamoorthy, 2016a , b ; Rakibuzzaman et al, 2021 ), with the exception that the genomes were dimerized to enable direct transfection and rescue without the need for excision and recircularization of the viral genome. In addition, a V5 tag encoding the amino acid sequence GKPIPNPLLGLDST was inserted into the 3′ end of the TTSuV1 ORF1 by overlap extension PCR and directional cloning to serve as a genetic and antigenic marker for the cloned TTSuV1 genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a V5 tag encoding the amino acid sequence GKPIPNPLLGLDST was inserted into the 3′ end of the TTSuV1 ORF1 by overlap extension PCR and directional cloning to serve as a genetic and antigenic marker for the cloned TTSuV1 genomic DNA. The TTSuV1 ORF1 gene was cloned and expressed as described before ( Singh and Ramamoorthy, 2016a , b ). The PCV1 rep was amplified using forward primer 5′-CTGAggatgcGCCACCATGCCCAGCAAGAAGAATG-3′ and reverse primer 5′-AGCTctcgagGTAATTTATTTCATATGGAAA-3′ from the PCV1 + PK15 cell cultures.…”
Section: Methodsmentioning
confidence: 99%